Persepsi Pemuda terhadap Pekerjaan sebagai Petani di Desa Klepu, Kecamatan Butuh, Kabupaten Purworejo - Muhammad Muflikhan; Eny Lestari; Suwarto Suwarto (AGRITEXTS: Journal of Agricultural Extension, 2024)
Agriculture is the primary support of a country, especially in rural areas. Klepu Village is a village in the Butuh Sub-district that still relies on agriculture as its main livelihood. However, the majority of farmers are now aged 40 and over. The younger generation tends to be more interested in working in other sectors than agriculture. This study examines and analyzes the perception of youth members of the Setya Bhakti youth organization in Klepu Village towards the farming profession. The research method used is descriptive qualitative. Informants were selected using purposive sampling with a total of 16 people consisting of leader and members of the youth organization, and the village head. The research data consists of primary and secondary data collected through in-depth interviews, observation, and documentation and validated using method triangulation and source triangulation. Data analysis was conducted using the interactive analysis method by Miles and Huberman. The study results indicate that the informants consider agriculture still viable for sustaining life in the village. Moreover, agriculture is still seen as a profession with good time flexibility, allowing work hours to be adjusted according to needs. Based on the interviews, the youth in Klepu Village are generally less interested in working in the agricultural sector. In the future, the government will pay more attention to the agricultural industry so that young people consider farming a viable livelihood.